Microsatellite data for Lobaria pulmonaria, Kuhmo, Finland - Snäll, Tord; Ronnås, Cecilia (Swedish University of Agricultural Sciences, 2019)
Microsatellite data from Lobaria pulmonaria (fragment lengths for each of the alleles).

For full details, see publication:
Ronnås, C., Werth, S., Ovaskainen, O., Várkonyi, G., Scheidegger, C., & Snäll, T. (2017). Discovery of long-distance gamete dispersal in a lichen-forming ascomycete. New Phytologist, 216(1), 216-226. https://doi.org/10.1111/nph.14714

Mikrosatellitdata för Lobaria pulmonaria, insamlade i Kuhmo i östra Finland.

För fullständig beskrivning, se:
Ronnås, C., Werth, S., Ovaskainen, O., Várkonyi, G., Scheidegger, C., & Snäll, T. (2017). Discovery of long-distance gamete dispersal in a lichen-forming ascomycete. New Phytologist, 216(1), 216-226. https://doi.org/10.1111/nph.14714
Mikrosatellitdata för lobaria pulmonaria (lunglav), Kuhmo, Finland - Mikrosatellitdata för lobaria pulmonaria (lunglav) Kuhmo, Finland
Keywords: BIOLOGICAL CLASSIFICATION; LICHENS; plant genetics; biology; biologi; short tandem repeats (STRs); korta tandemupprepningar (STRs); simple sequence repeats (SSRs); enkla sekvensupprepningar (SSR); Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Environment; Miljö